Who are you calling sub/urban? Socio-spatial inequality and mobility in the Lisbon Metropolitan Area - Santos, S. (Portuguese Journal of Social Science, 2016)
This article addresses the socio-territorial heterogeneity of the Lisbon Metropolitan Area (LMA) and its relationship with different types of mobility. We first use the 2011 Census to interpret the socio-demographic diversity of the LMA. We employ multivariate analysis to identify differentiating dimensions that distinguish between metropolitan parishes and use them to define groups. We then describe the mobility patterns of employees and students by constructing another typology of parishes (cluster analysis). Finally, we cross-reference the two typologies - socio-territorial and mobility - to show how space and society interact in the production of mobility in the LMA. The different patterns of mobility in the LMA are considered both a result and a reproduction factor of inequality in access to the metropolitan space.